Moisture dynamics and ageing in clarinet reeds by neutron radiography - Jongmin Lee; Qianru Zhan; Pavel Trtik; David Mannes (PLoS ONE, 2025)
The vibrational behavior of reeds in wind instruments is highly sensitive to their moisture content, yet the underlying hydration dynamics and their relationship to ageing remain poorly understood. In this study, we employ in situ neutron radiography to visualize and quantify internal water distribution in clarinet reeds at three stages of use: pristine, broken-in, and aged. Reeds were subjected to controlled wetting durations followed by drying under ambient conditions to enable time-resolved analysis of moisture uptake and retention. Neutron imaging revealed that water preferentially accumulates in the vamp region due to longitudinally exposed vascular structures, while the stock remains largely dry. Ageing significantly reduces both water uptake and retention capacity. Pristine reeds absorbed water rapidly and uniformly, whereas aged reeds exhibited faster drying; asymmetric moisture distribution; and non-uniform swelling and shrinkage, consistent with structural fatigue. These results demonstrate how repeated use alters hydration behavior and underscore the governing role of anatomical features, such as exposed vascular bundles and parenchyma cells. This study presents the first application of neutron imaging to clarinet reeds, providing spatially resolved insight into internal moisture dynamics. The findings establish a scientific basis for understanding reed break-in and ageing, with implications for performance optimization, reed design, and maintenance practices. Moreover, this work pioneers a novel application of neutron imaging in the study of woodwind instruments, where moisture control critically influences playability and longevity.